A reflex??o do docente sobre sua pr??tica no espa??o escolar - possibilidades e limites - Bretas, Rosana Maria (2007)
This research aims the teacher's reflection on his teaching praxis and it tries to investigate how it takes place within the school context. It searches not only to point the possibilities and the limits of the school to promote the reflection about the pedagogic action but also explores the hypothesis that the pedagogic project is a strategic space for the mobilization of the reflexive praxis and focuses the teachers' critical upbringing. It falls back upon the theoretical approach that holds up the tendency of the reflexive-teacher as well as at the developed ideas starting from Donald Sch??n's studies, the main formulator of this theory, and it tries to base itself in the comments about that tendency accomplished by some Brazilian authors that explore the matter in a critical-dialectic perspective. In addition to that perspective that goes over to contemplate on the pedagogic project as the stimulator of the reflection. Besides the bibliographical research, an investigation was also accomplished through semi-structured interviews with senior and high school teachers, in two different schools of the city of S??o Paulo, a private and a public state one. The results demonstrate that there is an acknowledgement of the reflection importance for the refinement of the teachers quality task and they still face limitations in order such reflection takes place indeed. The construction of the pedagogic project, that presupposes a collective work, it is pointed as an element that can make easy the convergence among the reflecting and the acting in the school space and to constitute a capable tool to revitalize educational and institutional experiences which enlarge the conscience and they become transformers of the reality.